Unique Findings of Sickle Cell Retinopathy in a Patient with Hemoglobin SE Disease - Corey Lacher; Aliya C. Roginiel; Elmira Baghdasaryan; Alexader A. Svoronos; Philip J. Ferrone; Isha Cheela (Journal of Ophthalmic & Vision Research)
Purpose: To report the second documented case of spontaneous sickle cell retinopathy due to hemoglobin SE disease, and the third in association with this condition overall. Case Report: An asymptomatic 19-year-old African American woman with hemoglobin SE disease and no other significant past medical history presented for a routine eye exam. Fundoscopy revealed two sunburst lesions in the temporal periphery of her right eye and one such lesion in the temporal periphery of her left eye. No definitive signs of neovascularization were detected on fluorescein angiography, although multiple areas of abnormal vasculature and distal nonperfusion were observed. Conclusion: Spontaneous peripheral retinopathy can develop at an early age in hemoglobin SE disease. Given the risk for complications, pediatric screening with regular fundoscopic examination may benefit such patients.